Centering Race to Move Towards an Intersectional Ecological Framework for Defining School Safety for Black Students. Issue 2 (3rd July 2021) - Edwards, Elianny C.
Abstract: Across time, frameworks for assessing school safety have failed to acknowledge the harm that institutional racism in school inflicts upon Black students. Such frameworks coupled with disparate outcomes resulting from policies meant to increase safety in schools have long begged the questions, "What does school safety look like for Black youth?" and "How do we promote it?" This manuscript calls for an intersectional ecological framework that considers racial–cultural, gender and queer identity, academic, social–emotional, interpersonal, and physical safety as critical dimensions of school safety for Black adolescents in middle and high school. This paper centers race—specifically Blackness—to offer a heuristic theoretical model for moving beyond colorblind paradigms of school safety. Implications for research and practice are also discussed. Impact Statement By highlighting the impact of institutional racism on Black students' safety, this manuscript offers important theoretical contributions to help inform how researchers define and assess school safety. This manuscript also highlights common, day-to-day systems and practices in schools that threaten the safety of Black students, and offers school leaders, teachers, and staff a vision of what school safety could look like for Black students in middle and high school.